Uncommodified Blackness : The African Male Experience in Australia and New Zealand - Majavu, Mandisi (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is a study of the lived experience of African men in Australia and New Zealand. The author employs a relational account of racism which foregrounds how the colonial shaped the contemporary, with the settler states of contemporary Australia and New Zealand having been moulded by their colonial histories. Uncommodified Blackness examines the changing racial conditions in Australia and New Zealand, inspired by the view that as racial conditions change globally, prevailing racial modalities in these two countries must be reexamined and theory must be developed or revised as appropriate. Students and scholars across a range of social science disciplines will find this book of interest, particularly those with an interest in refugees, immigration, race and masculinity.
Keywords: Social sciences.; Social structure.; Social inequality.; Sociology.; Ethnicity.; Emigration and immigration.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books